Kemampuan Pemahaman Konsep Matematis Ditinjau dari Kompetensi Keahlian - Afrida Adis Febriantika (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2019)
This research aimed to describe the mathematic conceptual understanding skills based on the expertise competency of grade X students of SMK Negeri 3 Purwokerto. This research applied the descriptive qualitative method. The sample was collected through the purposive sampling technique. This research collected two subjects from each of high and low achieving category in each expertise competency. The categories of high and low achieving students were based on the minimum required score. The data were collected through a test of mathematics conceptual understanding skills and interviews. The data were validated using the triangulation technique. The results of the research showed that (1) students of hotel accommodation department had a better mathematics conceptual understanding skill than students of the catering management department. It happened because the category of high achieving students of accommodation department fulfilled all indicators of mathematics conceptual understanding skills and the category of low achieving students of accommodation department only fulfilled the indicators of giving examples and non-examples from the concept being learned. (2) Students of catering management department had a better mathematic conceptual understanding skill than students of the fashion design department. It happened because the category of high achieving students of catering management department did not fulfill one indicator of presenting the concept in some forms of mathematic representations and the category of low achieving students of catering management department did not master all of the indicators. (3) The category of high achieving students of the fashion design department mastered all indicators of mathematics conceptual understanding skills of giving examples and non-examplesform the concept being learned and presenting the concept in some forms of mathematic representation. Meanwhile, the category of low achieving students of the fashion design department only mastered the indicator of applying concept or algorithm to problem-solving.